Digital Divides and the 'First Mile': Framing First Nations Broadband Development in Canada - Rob McMahon; Brian Beaton; Brian Walmark; Richard Smith; Susan O'Donnell; Rob McMahon; Susan O'Donnell; Richard Smith; Brian Walmark; Brian Beaton; Jason Simmonds (International Indigenous Policy Journal, 2011)
Across Canada, rural and remote First Nations face a significant 'digital divide'. As self-determining autonomous nations in Canada, these communities are building broadband systems to deliver public services to their members and residents. To address this challenge, First Nations are working towards a variety of innovative, locally driven broadband development initiatives. This paper contributes a theoretical discussion that frames our understanding of these initiatives by drawing on the paradigm of the 'First Mile' (Paisley & Richardson, 1998). We argue that broadband development policy in Canada must be re-framed to address the specific needs of First Nations. The First Mile position foregrounds community-based involvement, control, and ownership: a consideration we suggest has particular resonance for First Nations. This is because it holds potential to move beyond the historical context of paternalistic, colonial-derived development policies, in the context of broadband systems development. We argue First Nations broadband projects offer on-the-ground examples of a First Mile approach, and call for more research in this area.